2022
DOI: 10.7759/cureus.31540
|View full text |Cite
|
Sign up to set email alerts
|

“The Shelves Are Bare”: The Impact of COVID-19 on Families Enrolled in a Pediatric Produce Prescription Program

Abstract: A large pediatric clinic in Flint, Michigan, implemented a produce prescription program for youth to address enduring challenges with food access and food insecurity. Approximately 18 months later, on March 23, 2020, the State of Michigan issued a "stay home, stay safe" executive order in response to the COVID-19 pandemic. This study sought to (1) explore caregiver experiences with access to and utilization of the prescription program during COVID-19; and (2) understand perceived changes in the food environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…They also wanted to shop at Asian or Mexican grocery stores as well as stores with greater variety and higher quality produce, noting that in some cases they did not use the cards because of limited or low-quality produce. These findings are consistent with an evaluation of a produce prescription program in which participants reported that they had faced challenges with accessing high-quality fruits and vegetables before the COVID-19 pandemic and these challenges worsened during the pandemic ( 39 ). A study conducted by Lyonnais and colleagues found that participants reported that available locations where vouchers could be redeemed did not have the foods they were looking for and that this was a barrier to voucher redemption ( 29 ).…”
Section: Discussionsupporting
confidence: 85%
“…They also wanted to shop at Asian or Mexican grocery stores as well as stores with greater variety and higher quality produce, noting that in some cases they did not use the cards because of limited or low-quality produce. These findings are consistent with an evaluation of a produce prescription program in which participants reported that they had faced challenges with accessing high-quality fruits and vegetables before the COVID-19 pandemic and these challenges worsened during the pandemic ( 39 ). A study conducted by Lyonnais and colleagues found that participants reported that available locations where vouchers could be redeemed did not have the foods they were looking for and that this was a barrier to voucher redemption ( 29 ).…”
Section: Discussionsupporting
confidence: 85%
“…Although interest in research and healthcare policy related to food is medicine interventions is growing rapidly, programs prioritizing children are still limited. Only eight studies have aimed to understand the experience of caregivers in pediatric programs in the past decades (27)(28)(29)(30). In more recent qualitative studies of pediatric produce prescription programs operated during the COVID-19 pandemic, themes from the perspectives of caregivers revealed exacerbated economic challenges related to the pandemic, adaptations made in response to program implementation, and perceived favorable program effects on healthy food access and family dietary habits (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Only eight studies have aimed to understand the experience of caregivers in pediatric programs in the past decades (27)(28)(29)(30). In more recent qualitative studies of pediatric produce prescription programs operated during the COVID-19 pandemic, themes from the perspectives of caregivers revealed exacerbated economic challenges related to the pandemic, adaptations made in response to program implementation, and perceived favorable program effects on healthy food access and family dietary habits (28)(29)(30). These previous studies underscored the diversity of experiences with produce prescription program, which could be affected geographic and temporal factors.…”
Section: Introductionmentioning
confidence: 99%